Examination of Turkish-made products with the theory of planned behavior: A research on regular migrants in Turkey - Narci, Muhammed Talha (Journal of Asian Scientific Research, 2024)
This paper investigates the examination of Turkish-made products with the theory of planned behavior. The exploration of regular immigration, encompassing individuals relocating to other countries either temporarily or permanently for various reasons, stands as a prominent subject in current international research. This article examines the attitudes of regular immigrants towards products made in Turkey, employing the theory of planned behavior. In the research, where the quantitative research method was followed, regular immigrants residing in Turkey were selected as the research population. A survey was used as a data collection technique in the research, and the prepared survey form was applied online to regular immigrants currently residing in Turkey, and 444 responses were obtained. The obtained data were analyzed using AMOS and SPSS 26.0 statistical programs, and according to the research questions, correlation and regression analyses were applied. The findings showcase that the attitudes, subjective norms, and perceived behavioral controls of regular immigrants towards Turkish-made products significantly influence their behavioral intentions. Moreover, these intentions have a positive effect on their actual product usage or purchases. Notably, individuals exhibit favorable behavioral intentions towards Turkish products, which has a significant positive effect on their purchasing behavior. Since this study focuses specifically on Turkey, a host to one of the largest immigrant populations globally, and aims to dissect the impact of migrated country products on consumption preferences in multiple ways, it is important.